NILAI GIZI DAN KARAKTERISTIK FISIK SERTA FISIKOKIMIA PATI UMBI SUWEG (Amorphophalus campanulatus) - . Tejasari (JURNAL AGROTEKNOLOGI, 2007)
Suweg (Amorphophalus campanulatus Deene) starch could be one of local alternative foodstuff for food diversification. Knowing its characteristic is important especially for determination its storage method, its processing technology, and suitability kinds of processed food. This study was conducted to determine its physical and physicochemical characteristics, and its nutritional value. The experiment showed that one-kilogram of fresh suweg tuber root yielded 73.5 gram of starch. Suweg starch has white color expressed by 97.3 whiteness degree. Its granule is polygonale irregular form, and has about 20-30 μm size. The starch has space density by 0.69, and its pouring makes at an angle of 39.60 o. Its gel consistency is soft(96.44mm). Other physicochemical characteristics of the starch are low paste viscosity, water absorption, and water soluble value by 0.0056 pa.det, 2.15 , 0.05 percent, respectively. These characteristics are suitable for food that do not need high blow up in nature, such as biscuit and noodles. Suweg starch is nutritious foodstuff, especially its high carbohydrate, sufficient fat, and mineral contains, respectively by 87.2, 5.5 , 1.6 g per 100 g in starch on dry basis (d.b). Suweg starch still have protein (0.6 percent) and crude fibre (0.04 percent). Keywords: suweg starch, physics and physicochemical characteristics, nutritional value